2006
DOI: 10.1590/s0100-879x2006000900010
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the promoter region and exon 1 of the CTLA4 gene in endemic pemphigus foliaceus (fogo selvagem)

Abstract: Endemic pemphigus foliaceus (EPF) is an autoimmune bullous skin disease characterized by acantholysis and antibodies against a desmosomal protein, desmoglein 1. Genetic and environmental factors contribute to development of this multifactorial disease. HLA class II and some cytokine gene polymorphisms are the only genetic markers thus far known to be associated with susceptibility to or protection from EPF. The cytotoxic T-lymphocyte antigen-4 gene (CTLA4) encodes a key immunoreceptor molecule that regulates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Several studies have confirmed that CTLA-4 polymorphism is associated with MG [18 -20]. Recently, Pavoni et al studied the influence of CTLA4 Ϫ318 and ϩ49 polymorphisms in the pathogenesis of PF; however, no statistically significant association between PF and variants of the CTLA4 gene was observed [21], similar to our results. On the other hand, in our study the frequency of the G/G ϩ49 genotype, associated with a reduced control of T-cell activation and in this way probably contributing to the pathogenesis, was increased in PV patients compared with healthy individuals.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have confirmed that CTLA-4 polymorphism is associated with MG [18 -20]. Recently, Pavoni et al studied the influence of CTLA4 Ϫ318 and ϩ49 polymorphisms in the pathogenesis of PF; however, no statistically significant association between PF and variants of the CTLA4 gene was observed [21], similar to our results. On the other hand, in our study the frequency of the G/G ϩ49 genotype, associated with a reduced control of T-cell activation and in this way probably contributing to the pathogenesis, was increased in PV patients compared with healthy individuals.…”
Section: Discussionsupporting
confidence: 87%
“…However the absence of significant associations has been reported in a previous study of -318CϾT and 49AϾG SNPs in a cohort of 118 PF patients and 291 control subjects [28]. In a recent study of pemphigus, the CTLA4 49*G allele and G/G genotype frequencies were slightly increased among 48 patients, of whom 37 had pemphigus vulgaris, but no association was found either [45].…”
Section: Discussionmentioning
confidence: 84%
“…To improve efficacy and specificity, we performed a nested PCR using the same forward primer and oligonucleotide 5=-TTTTAGGG-TACATGTGCACAACA-3= as reverse primer, resulting in a fragment of 367 bp. The segment, including the SNPs -318CϾT (rs5742909) and 49AϾG (rs231775), was amplified by PCR and hybridized with the sequence-specific oligonucleotide probes (PCR-SSOP) as described by Pavoni et al [28]. The 6230GϾA (or CT60 SNP, rs3087243) in the 3=UTR was typed in the same population samples in a previous study [29].…”
Section: Genotyping Of Ctla4 Snpsmentioning
confidence: 99%
“…[22][23][24] Associations were found also with interleukin 6, interleukin 4 25 and programmed cell death 1 genotypes 26 but not with the TNF, lymphotoxin-a, DSG1 polymorphisms, cytotoxic T-lymphocyte antigen-4 gene, BAX and TP53 polymorphisms. [27][28][29][30] This is typical for multifactorial (complex) diseases, with several genetic and environmental factors involved in etiology and pathogenesis, and justifies the search for other genes modulating the susceptibility to PF.…”
Section: Introductionmentioning
confidence: 99%